2002
DOI: 10.4161/cbt.1.5.164
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Occurring Allele of BRCA1 Coding for a Temperature-Sensitive Mutant Protein

Abstract: © 2 0 0 2 L a n d e s B i o s c i e n c e . N o t f o r d i s t r i b u t i o n .[Cancer Biology & Research PaperA Naturally Occurring Allele of BRCA1 Coding for a TemperatureSensitive Mutant Protein ABSTRACT Recent evidence suggests that the breast and ovarian cancer susceptibility gene product BRCA1 is involved in at least two fundamental cellular processes: transcriptional regulation and DNA repair. However, the mechanism of action of BRCA1 in either of these processes is still unknown. Here, we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
1
18
1
1
Order By: Relevance
“…More than 70 missense substitutions have been recorded that alter the primary sequence of the tandem BRCT repeats, but pedigree analysis clarifying the disease linkage of these alleles is available for only eight of these variants (6,7,12,(23)(24)(25)(26)(27). Many of these amino acid substitutions may be linked with disease but remain as unclassified in the BIC, because the presence of the allele has not been tested in the general population, or the segregation of the allele with disease within a family is unclear (6, 7).…”
mentioning
confidence: 99%
“…More than 70 missense substitutions have been recorded that alter the primary sequence of the tandem BRCT repeats, but pedigree analysis clarifying the disease linkage of these alleles is available for only eight of these variants (6,7,12,(23)(24)(25)(26)(27). Many of these amino acid substitutions may be linked with disease but remain as unclassified in the BIC, because the presence of the allele has not been tested in the general population, or the segregation of the allele with disease within a family is unclear (6, 7).…”
mentioning
confidence: 99%
“…The aims in this proposal were performed by two fellows: Blase Billack (2002 and who left for a faculty position in breast cancer research and Vesna Dapic (2004). During our characterization of the R1699W mutant and of the other temperature-sensitive mutants isolated in yeast 25, 26 we found that these mutants were not yet widely applicable as tools.…”
Section: Bodymentioning
confidence: 99%
“…The pathogenicity of only a small number of these variants has been inferred genetically [12][13][14][15][16] or tested functionally [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Underscoring the interest in and need for accurate classification of sequence variants in BRCA1 are recent descriptions of novel approaches to predict the pathogenicity of non-synonymous amino acid substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…A multiple sequence alignment of fulllength BRCA2 cDNA sequences was generated using the T-coffee program (29). The alignment was restricted to BRCA2 cDNA sequences derived from vertebrates in an effort to avoid using sequences that are evolutionarily 4 S.V.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation